The void protocol - Wilson, F. Paul (Francis Paul) (Wilson, F. Paul (Francis Paul), Ice trilogy, 2019)
"Something sits in a bunker lab buried fifty feet below the grounds of Lakehurst Naval Air Station. The product of technology confiscated from the Germans after WWII occupies a chamber of steel-reinforced ballistic glass. Despite experimentation for nearly three-quarters of a century, no one knows what it is, but illegal human research reveals what it can do. Humans with special abilities--abilities that can only have come from whatever occupies the underground bunker in Lakehurst--have been secretly collected. And so it sits, sequestered on the edge of the New Jersey Pine Barrens, slowly changing the world" --